2021
DOI: 10.3390/ijms22041674
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial and Human Ferrous Nitrobindins: Spectroscopic and Reactivity Properties

Abstract: Structural and functional properties of ferrous Mycobacterium tuberculosis (Mt-Nb) and human (Hs-Nb) nitrobindins (Nbs) were investigated. At pH 7.0 and 25.0 °C, the unliganded Fe(II) species is penta-coordinated and unlike most other hemoproteins no pH-dependence of its coordination was detected over the pH range between 2.2 and 7.0. Further, despite a very open distal side of the heme pocket (as also indicated by the vanishingly small geminate recombination of CO for both Nbs), which exposes the heme pocket … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 76 publications
(120 reference statements)
0
7
0
Order By: Relevance
“…The absorbance spectra of Mt -Nb(II)-NO, At -Nb(II)-NO, Dr -Nb(II)-NO, and Hs -Nb(II)-NO, obtained by NO 2 − reduction, overlapped with those achieved by flowing gaseous NO in Mt -Nb(II), At -Nb(II), Dr -Nb(II), and Hs -Nb(II) solutions. Interestingly, the absorbance spectra of Mt -Nb(II)-NO, At -Nb(II)-NO, Dr -Nb(II)-NO, and Hs -Nb(II)-NO reflected the cleavage or the severe weakening of the proximal His-Fe(II) bond as evidenced from EPR spectroscopy [ 21 , 23 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The absorbance spectra of Mt -Nb(II)-NO, At -Nb(II)-NO, Dr -Nb(II)-NO, and Hs -Nb(II)-NO, obtained by NO 2 − reduction, overlapped with those achieved by flowing gaseous NO in Mt -Nb(II), At -Nb(II), Dr -Nb(II), and Hs -Nb(II) solutions. Interestingly, the absorbance spectra of Mt -Nb(II)-NO, At -Nb(II)-NO, Dr -Nb(II)-NO, and Hs -Nb(II)-NO reflected the cleavage or the severe weakening of the proximal His-Fe(II) bond as evidenced from EPR spectroscopy [ 21 , 23 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…A dramatic example is represented by tetrameric Hs -Hb(II) in the R-state, Pc -Mb(II) and Hs -Nb(II), which all displayed values of k on(NO2−) ~ 6.0 M −1 s −1 while values of the CO-binding rate constant greatly differed, spanning between 1.0 × 10 7 M −1 s −1 and 1.0 × 10 5 M −1 s −1 ( Figure 5 , panel B, and Table 1 ). Although multiple conformations of both the distal and the proximal side of the heme pocket affect the CO-binding rate constant [ 79 , 80 ], a likely structural explanation has been attributed to the activation free energy for the ligand-induced movement of the Fe(II) atom into the heme plane, which is fairly low for tetrameric Hs -Hb(II) in the R-state, while it seems very high for Hs -Nb(II) [ 23 , 79 ]. As a matter of fact, it has been convincingly shown that a major contribution to the reactivity of CO with hemoproteins is represented by the energy required for the movement of the heme’s Fe atom from its unliganded position (about 0.5 Ǻ out of the heme plane on the proximal side) to the heme co-planar position in the CO-liganded form [ 2 , 79 , 81 ]; the major contribution stems from the steric repulsion between the imidazole of the proximal histidine and the heme pyrroles, which depends on the relative position and differs among various hemoproteins [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most striking differences between the 2/2 and the 3/3 globin folds are: ( i ) the drastically shortened or absent A-helix, ( ii ) the alteration of the C-E region, and ( iii ) the presence of a long polypeptide segment, which precedes the short α-helix F where the proximal HisF8 residue is located coordinating the heme-Fe atom [ 2 , 4 , 7 , 8 , 21 ]. Over the last two decades, all β-barrel non-canonical globins (i.e., nitrophorins and nitrobindins) mainly devoted to NO metabolism have been reported [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Of note, human nitrobindin, corresponding to the C -terminal domain of the nuclear protein THAP4, has been hypothesized to act as a NO sensor modulating the transcriptional activity residing at the N -terminus [ 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last two decades, all β-barrel non-canonical globins (i.e., nitrophorins and nitrobindins) mainly devoted to NO metabolism have been reported [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Of note, human nitrobindin, corresponding to the C -terminal domain of the nuclear protein THAP4, has been hypothesized to act as a NO sensor modulating the transcriptional activity residing at the N -terminus [ 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%